European border regions in comparison
1 online resource (ix, 379 pages)
Keywords: "Borders exist in almost every sphere of life. Initially, borders were established in connection with kingdoms, regions, towns, villages and cities. With nation building, they became important as a line separating two national states with different "national characteristics," narratives and myths. The term "border" has a negative connotation for being a separating line, a warning signal not to cross a line between the allowed and the forbidden. The awareness of both mental and factual borders in manifold spheres of our life has made them a topic of consideration in almost all scholarly disciplines: history, geography, political science and many others. This book primarily incorporates an interdisciplinary and comparative approach. Historians, sociologists, anthropologists and political science scholars from a diverse range of European universities analyze historical as well as contemporary perceptions and perspectives concerning border regions -- inside the EU, between EU and non-EU European countries, and between European and non-European countries"--